Impact of anticoagulation strategy with bivalirudin or heparin on nonaccess site bleeding in percutaneous coronary interventions: A meta‐analysis of randomized trials. Issue 4 (4th May 2017) - Verdoia, Monica; Barbieri, Lucia; Parodi, Guido; Bellandi, Benedetta; Schaffer, Alon; Suryapranata, Harry; De Luca, Giuseppe
Abstract : Background: Transradial approach has significantly decreased the rate of access site bleeding in patients undergoing percutaneous coronary interventions (PCI), therefore potentially mitigating the benefits offered by bivalirudin in lowering major bleeding complications as compared to heparin. However, nonaccess site bleeding, that represent the majority of hemorrhagic complications, still carry negative prognostic consequences for these patients and no study has so far defined the exact impact of bivalirudin on nonaccess site bleeding, that was therefore the aim of present meta‐analysis. Methods and study outcomes: Literature archives (Pubmed, EMBASE, Cochrane) and main scientific sessions were scanned comparing bivalirudin vs. heparin in patients undergoing PCI. Primary endpoint was the occurrence of nonaccess site bleeding within 30 days. Secondary endpoints were 30 days mortality and the occurrence of access‐site bleeding. Results: A total of nine randomized clinical trials were finally included, involving 32, 587 patients, 55.8% randomized to bivalirudin. Bivalirudin significantly reduced the rate of nonaccess site bleeding (2.6 vs. 3.8%, OR [95% CI] = 0.68 [0.60–0.77], P  < 0.00001, P het  = 0.10). However, the reduction of hemorrhagic events was more pronounced when bivalirudin was compared to heparin plus glycoprotein IIbIIIa inhibitors than when it was compared to heparin alone ( r  = −0.01 (−0.02; −0.001), P  = 0.02). Similar results were observed for access‐site bleeding (OR [95% CI] = 0.67 [0.57–0.79], P  < 0.000001, P het  = 0.10), with a significant role of glycoprotein IIbIIIa inhibitors use ( r  = −0.02 (−0.04; −0.004), P  = 0.017). Moreover, the observed benefits in hemorrhagic complications did not translate into mortality benefits (OR [95% CI] = 0.89 [0.76–1.05], P  = 0.18; P het  = 0.12; r  = 0.21 (−1.12; 1.53), P  = 0.76). Conclusions: The present meta‐analysis shows that bivalirudin can provide a significant reduction of both access and nonaccess site bleeding in patients undergoing PCI. However, these hemorrhagic benefits did not impact on survival, and moreover, were significantly conditioned by the association of heparin with potent antithrombotic strategies, such as glycoprotein IIbIIIa inhibitors, rather than by heparin or bivalirudin alone. Therefore, we could not provide any clinical evidence for the routine use of bivalirudin as preferred anticoagulation strategy for PCI. © 2017 Wiley Periodicals, Inc.